Arrangements of Involuntary Treatment for People with Mental Disorders in Indonesia - I Gde Yudhi Kurniawan; Made Suksma Prijandhini Devi Salain; Luh Nyoman Alit Aryani; I Nyoman Prabu Buana Rumiartha (Jurnal Hukum Prasada, 2025)
Mental disorders are health conditions where individuals experience changes in thinking patterns, emotions, or behavior, or a combination of these changes. During relapses, it is not uncommon for individuals with mental disorders to refuse treatment or therapy prescribed by doctors. Involuntary treatment for individuals with mental disorders (ODGJ) sometimes becomes an unavoidable option if there is a risk of harm to themselves or others. This research is a normative legal study aimed at examining the implementation of involuntary treatment for ODGJ in Indonesia and several other countries, using a legislative and comparative approach. The Indonesian Health Law (2023) does not specifically regulate involuntary treatment but implicitly addresses it in Article 80, paragraphs (1) to (5). There are vague norms regarding the criteria for involuntary treatment, its duration, and the patient's right to review the treatment they receive. In some countries, there are clear criteria regarding the conditions for involuntary treatment, family obligations, and its duration. In the derivative regulations, it is recommended to include the necessary additional criteria to create legal certainty and protection for medical personnel, as well as for patients and their families.